Primacy of the leader, obscuration of followers: The discourse of leadership in the business media. (June 2019) - Tessema, Kedir Assefa
Highlights: The business media engages in the discursive process of leadership discourse. The leadership discourse is leader-centric and market motive driven. The leadership construction places primacy on the leader's dispositions and agency. The construction does not only place primacy on the leader, it also obscures followers. Abstract: The study explored the construction of leadership in the business media by focusing on four widely read online business e-magazines. Using Foucauldian discourse analysis, a sample of 806 online e-magazine articles published between 2015 and 2018 were systematically studied. The construction does not only grant primacy to the leader, but also it obscures followers and other secondary social actors. The study contributes to existing literature on leadership representation, leadership stakeholders involved in such discursive process, and their routine practices of writing leadership texts that legitimize certain meanings at the expense of others. The paper suggests that such a construction of leadership in the business media impacts both followers' and aspiring leaders' perceptions, ultimately limiting what can be envisioned and enacted.